1998
DOI: 10.1016/s0927-0256(97)00180-8
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure calculations of vacancies and their influence on materials properties

Abstract: August 1997This is a preprint of a paper intended for publication in a journal or proceedings. Since changes may be made before publication, this preprint is made available with the understanding that it will not be cited or reproduced without the permission of the author. PREPRINTThis paper was prepared for submittal to the DISCLAIMER This document was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor the University of California no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…It is therefore important to examine void swelling mechanisms for any significant future density changes. While this ratio is corroborated by the observation from TEM and positron annihilation measurements [5][6][7], a significant variation exists between specimens, see Table 3. Even 2 and 3 cm length specimens at 35°C, which represent bulk changes, show different values of 2.66 and 1.83.…”
Section: Volumetric Swelling Analysissupporting
confidence: 59%
See 2 more Smart Citations
“…It is therefore important to examine void swelling mechanisms for any significant future density changes. While this ratio is corroborated by the observation from TEM and positron annihilation measurements [5][6][7], a significant variation exists between specimens, see Table 3. Even 2 and 3 cm length specimens at 35°C, which represent bulk changes, show different values of 2.66 and 1.83.…”
Section: Volumetric Swelling Analysissupporting
confidence: 59%
“…The helium that accumulates in plutonium immediately finds an unfilled vacancy and forms bubbles inside the crystalline matrix and along grain boundaries [5][6][7]. The dilatometry shows volume expansion at a steady rate with time primarily induced by a constant helium in-growth rate of ~41.1 appm per year, whereas the data of Chebotarev and Utkina do not [4].…”
Section: Physical Interpretation Of Volumetric Swellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The second determination of the helium density in bubbles was obtained by Sterne et al [20] with positron annihilation lifetime measurements on old plutonium samples and with first-principles calculations of annihilation rates of positrons trapped in vacancy clusters, voids and helium bubbles. These calculations have shown that calculated positron lifetimes in old plutonium samples agree with the measured values of 180-200 ps if the He/Vac.…”
Section: The Effect Of Helium On Densitymentioning
confidence: 99%
“…Electronic structure calculations contribute to our understanding of vacancies and their role in determining materials properties [1]. Diffusion is known to depend strongly on vacancies.…”
mentioning
confidence: 99%